Tuberculous lymphadenitis associated with human immunodeficiency virus (HIV) in Uganda. Issue 1 (January 1988) - Nambuya, A; Sewankambo, N; Mugerwa, J; Goodgame, R; Lucas, S
Abstract : Sixteen adults presented with lymphadenopathy which was tuberculous on biopsy; they were all seropositive for human immunodeficiency virus (HIV-1), but none had the clinical criteria of the acquired immunodeficiency syndrome (AIDS). The biopsy specimen showed caseating tuberculosis, with scanty or no visible acid fast bacilli in seven cases; the remaining nine had a poor cellular reactivity with numerous bacilli. Antituberculous chemotherapy for two months reduced the lymphadenopathy. Two patients subsequently developed AIDS. Mycobacterial cultures were not performed, but the infection was almost certainly Mycobacterium tuberculosis. The space-time clustering of tuberculous lymphadenitis now seen in Kampala, and the unusual non-reactive histopathology, are typical of the impairment of cellular immunity induced by HIV infection.